2004
DOI: 10.1523/jneurosci.0965-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

The Construction of Movement with Behavior-Specific and Behavior-Independent Modules

Abstract: Growing evidence suggests that different forms of complex motor acts are constructed through flexible combinations of a small number of modules in interneuronal networks. It remains to be established, however, whether a module simply controls groups of muscles and functions as a computational unit for use in multiple behaviors (behavior independent) or whether a module controls multiple salient features that define one behavior and is used primarily for that behavior (behavior specific). We used the Aplysia fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
122
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(133 citation statements)
references
References 38 publications
10
122
0
1
Order By: Relevance
“…The current results and other recent findings (Svoboda and Fetcho, 1996 2005) suggest that generation of several types of vertebrate hindlimb motor patterns may be mediated by a combination of shared and specialized circuitry, as has been seen in more numerous and detailed studies in invertebrates (Morton and Chiel, 1994;Marder and Calabrese, 1996;Kristan and Shaw, 1997;Edwards et al, 1999;Kupfermann and Weiss, 2001;Jing et al, 2004;Briggman et al, 2005;Marder et al, 2005;Briggman and Kristan, 2006). Moreover, the current results and a recent study in zebrafish (Ritter et al, 2001) both suggest that these shared and specialized subsets of spinal interneurons may to some extent be morphologically distinguishable.…”
Section: Morphological Comparisons To Dorsal Horn Cells In Other Studiessupporting
confidence: 79%
See 1 more Smart Citation
“…The current results and other recent findings (Svoboda and Fetcho, 1996 2005) suggest that generation of several types of vertebrate hindlimb motor patterns may be mediated by a combination of shared and specialized circuitry, as has been seen in more numerous and detailed studies in invertebrates (Morton and Chiel, 1994;Marder and Calabrese, 1996;Kristan and Shaw, 1997;Edwards et al, 1999;Kupfermann and Weiss, 2001;Jing et al, 2004;Briggman et al, 2005;Marder et al, 2005;Briggman and Kristan, 2006). Moreover, the current results and a recent study in zebrafish (Ritter et al, 2001) both suggest that these shared and specialized subsets of spinal interneurons may to some extent be morphologically distinguishable.…”
Section: Morphological Comparisons To Dorsal Horn Cells In Other Studiessupporting
confidence: 79%
“…Cellular mechanisms of behavioral choice are best understood for several invertebrate systems, in which many CNS neurons contribute to multiple behaviors, whereas others are dedicated to just one (Morton and Chiel, 1994;Marder and Calabrese, 1996;Kristan and Shaw, 1997;Edwards et al, 1999;Kupfermann and Weiss, 2001;Jing et al, 2004;Briggman et al, 2005;Marder et al, 2005;Briggman and Kristan, 2006). In some cases, CNS neurons dedicated to one behavior inhibit CNS neurons dedicated to another behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has proposed the existence of movement control modules (Grillner, 1981(Grillner, , 1985Loeb, 1985;Bizzi et al, 1991), for which there is evidence in both vertebrates (Tresch et al, 2002 (Jing et al, 2004). Control modules incorporating both neural and biomechanical components may be referred to as "neuromechanical modules."…”
Section: Neuromechanical Modulesmentioning
confidence: 99%
“…The interneuronal mechanisms that generate different feeding motor patterns in Aplysia have been studied intensively Weiss, 2001, 2002;Jing et al, 2004) using neural patterns identified through in vitro recordings of individual identified neurons or nerves. For example, to discriminate biting from swallowing, the authors use the duration of activity in the I2 motor neurons (Jing et al, 2004).…”
Section: Implications For Pattern Generationmentioning
confidence: 99%
See 1 more Smart Citation